Rare bird documentation form for Glaucous Gull at Lock and Dam 15 in 1983 - White, Geraldet al (1983)
Rare bird documentation form for a Glaucous Gull near Lock and Dam 15 in Davenport in January 23, 1983. Epson - sheet feed